Die Wohn- und Siedlungskonzentration in Hong Kong als Beispiel einer extremen städtischen Verdichtung - Buchholz, Hanns Jürgen (ERDKUNDE, 1973)
In comparison to many other world cities the population density of Hong Kong is not very high. But in Hong Kong the distribution of the population is very disproportionate. About 83% of the Hong Kong land population live in Hong Kong Island, Kowloon, and New Kowloon and within this urban area 90% of the population live on 10% of the whole land area (Fig. 2). Several statistical units (tertiary units) have more than 200.000 persons per sq. kilometer. (Census 1971; Fig. 1.) As an example one part of Yau Ma Tei (Kowloon) is analyzed in more detail. Here the average plot ratio is 6.24! The average usable floor area comes to about 3.50 sq. meters per person. If we look to the relation between density and protection, density and anonymity, density and carrying capacity and division of labour, density and attractivity, density and frequency of contacts, we can see that within this area the whole situation - extreme building coverage and plot ratio, very high occupancy rate, and the over crowded streets - turns the advantages of urban density into the opposite. In particular the unavoidable contacts with other people even within tenements and rooms will lead to psychological conflicts. The highest tolerable population density seems to be about 100.000 persons per sq. kilometer within this part of Kowloon.